A multi-enzyme cascade hydrogel for diabetic foot wound repair and a preparation method and application thereof

CN122998455APending Publication Date: 2026-10-30COMPREHENSIVE REGIONAL MEDICAL CENTER BENGBU HOSPITAL (THE SECOND AFFILIATED HOSPITAL OF BENGBU MEDICAL UNIVERSITY)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611376486.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]本发明的第一目的在于提供一种糖尿病足创面修复用多酶级联水凝胶,旨在解决现有技术中多酶活性位点空间分布无序、底物传质效率低、级联反应效率不高、功能集成度不足以及缺乏可注射自愈合递送载体等问题

Benefits of technology

[0022](1)本发明提供了一种核壳表面负载型金铈级联纳米酶(CeZ@Au),其中CeO2纳米核在生理条件下具有过氧化氢酶(CAT)和过氧化物酶(POD)双重酶样活性,可生成羟基自由基杀菌或生成O2改善缺氧;ZIF-8壳层在生理条件下稳定、在酸性环境下分解并缓慢释放Zn²⁺,有利于加快伤口愈合且具有一定抑菌作用;表面锚定的AuNPs具有类葡萄糖氧化酶(GOx)活性,能够催化氧化葡萄糖产生葡萄糖酸和H2O2。三种功能组分协同形成具有CAT、GOx、POD三种酶样活性的级联纳米酶体系,此前未见报道。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998455A_ABST
    Figure CN122998455A_ABST
Patent Text Reader

Abstract

The application discloses a kind of multi-enzyme cascade hydrogel for the repair of diabetic foot wound and preparation method thereof.The hydrogel includes CeO2@ZIF-8 / Au cascade nanoenzyme, astragalus polysaccharide-derived carbon quantum dots, methacryl carboxymethyl chitosan, dopamine-modified hyaluronic acid, oxidized dextran and photoinitiator.The CeO2@ZIF-8 / Au cascade nanoenzyme is composed of cerium dioxide nanoparticles, ZIF-8 shell and gold nanoparticles loaded on the shell surface;The astragalus polysaccharide-derived carbon quantum dots are prepared by hydrothermal carbonization of astragalus polysaccharide;Both are loaded in the double-crosslinked hydrogel network formed by Schiff base dynamic crosslinking and photoinitiator crosslinking.The hydrogel has injectability, self-healing and tissue adhesion, and is suitable for filling and attaching to the diabetic foot wound.It can adapt to irregular wound shape and firmly adhere to wound tissue, and through the synergistic effect of cascade nanoenzyme and astragalus CDs, it realizes the systematic regulation of oxidative stress, bacterial infection, tissue hypoxia and high-sugar microenvironment of diabetic wound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanobiomedical materials technology, specifically relating to a multi-enzyme cascade hydrogel with triple mimic enzyme activities of glucose oxidase, catalase and peroxidase, its preparation method and its application in the preparation of drugs or medical dressings for the treatment of diabetic foot ulcers. Background Technology

[0002] Diabetes mellitus is a chronic metabolic disease characterized by persistently elevated blood glucose levels. The number of adults with diabetes worldwide has exceeded 800 million, more than quadrupling since 1990, and is projected to reach 1.3 billion by 2050. Among the various complications associated with diabetes, diabetic wounds (DWs), especially diabetic foot ulcers (DFUs), pose a significant clinical challenge due to their complexity and poor healing. The core pathological mechanisms underlying the difficulty in healing DFUs include: (1) a persistently hyperglycemic environment at the wound site leading to the accumulation of advanced glycation end products (AGEs), inducing a strong oxidative stress response, resulting in excessive generation of reactive oxygen species (ROS) and triggering a cascade of inflammation; (2) repeated bacterial infections forming biofilms, further exacerbating inflammation and hindering tissue regeneration; and (3) local vascular lesions leading to ischemia and hypoxia, hindering angiogenesis. In response to these complex pathological mechanisms, multi-enzyme cascade nanozyme systems exhibit unique therapeutic advantages. Gold nanoparticles (AuNPs) have been shown to possess glucose oxidase (GOx)-like functions, catalyzing the oxidation of local glucose in wounds to generate gluconic acid and H2O2. CeO2 nanoparticles possess dual enzymatic activity of catalase (CAT) and peroxidase (POD), catalyzing the generation of hydroxyl radicals (·OH) from H2O2 for sterilization or decomposition to generate O2 to improve hypoxia. Zeolite imidazole salt framework-8 (ZIF-8) decomposes and slowly releases Zn²⁺ in acidic infection microenvironments, which is beneficial for accelerating wound healing and has antibacterial effects. Carboxymethyl chitosan is a common chitosan derivative with good water solubility, biocompatibility, and antibacterial activity, and is therefore widely used in wound dressings. However, the existing technology still has the following defects: (1) The spatial distribution of multi-enzyme active sites is disordered, the substrate mass transfer efficiency is low, and the cascade reaction efficiency is not high. Most of the existing nanozyme systems combine various functional components through physical mixing, resulting in weak synergistic effects and a lack of responsiveness to the microenvironment of different healing stages of the wound; (2) The functional integration is insufficient. Most of the existing hydrogels only carry a single or a few active ingredients, making it difficult to systematically and synergistically regulate the complex pathological microenvironment of diabetic wounds (oxidative stress, bacterial infection, tissue hypoxia, hyperglycemia, etc.); (3) Existing nanozymes lack injectable, self-healing, and other multifunctional hydrogel delivery carriers, making it difficult to achieve long-term retention and on-demand release at the wound site; (4) The source of carbon quantum dots is singular. The application of plant-derived functional carbon quantum dots in diabetic wound dressings is still relatively limited, and there is still room for further expansion in the research and application of the synergistic construction of Astragalus polysaccharide-derived carbon quantum dots and multi-enzyme-like cascade systems. Therefore, developing a novel delivery system that can organically integrate multi-enzyme cascade nanozymes, astragalus-derived carbon quantum dots, and multifunctional hydrogel carriers is of great clinical significance and application value for the efficient treatment of diabetic foot ulcers. Summary of the Invention

[0003] The primary objective of this invention is to provide a multi-enzyme cascade hydrogel for repairing diabetic foot wounds, aiming to solve problems in the prior art such as disordered spatial distribution of multi-enzyme active sites, low substrate mass transfer efficiency, low cascade reaction efficiency, insufficient functional integration, and lack of injectable self-healing delivery carriers.

[0004] To achieve the above objectives, this invention provides a multi-enzyme cascade hydrogel for repairing diabetic foot wounds, which integrates CeO2@ZIF-8 / Au cascade nanozymes, astragalus polysaccharide-derived carbon quantum dots, and an injectable, adhesive, double-crosslinked hydrogel carrier. Specifically, the CeO2@ZIF-8 / Au cascade nanozymes and astragalus polysaccharide-derived carbon quantum dots are co-dispersed within a double-crosslinked hydrogel network formed by methacryloylcarboxymethyl chitosan (CMCSMA), dopamine-modified hyaluronic acid (HA-DA), and oxidized dextran (ODex).

[0005] The core-shell surface-supported gold-cerium cascade nanozyme uses CeO2 nanoparticles as the core and ZIF-8 as the shell, with gold nanoparticles (AuNPs) anchored and loaded on the outer surface of the ZIF-8 shell. The CeO2 nanoparticles possess dual mimicry activities of catalase (CAT) and peroxidase (POD), while the AuNPs possess glucose oxidase (GOx) mimicry activities. This nanozyme simultaneously exhibits triple mimicry activities of GOx, CAT, and POD, enabling it to catalyze a cascade reaction: AuNPs catalyze the oxidation of glucose to H2O2, and the CeO2 nanoparticles further catalyze the decomposition of H2O2 to generate ·OH (for sterilization) and / or O2 (to improve oxygenation).

[0006] The hydrogel is formed through a dual cross-linking process: Schiff base reaction (amino group of CMCSMA reacts with aldehyde group of ODex) and photocross-linking (methacrylamide groups on CMCSMA polymerize under blue light in the presence of a photoinitiator).

[0007] As a further description of the above technical solution:

[0008] The CeO2 nanoparticles have a dynamic light scattering hydrated particle size of 247.87±0.74 nm and a polydispersity index of 0.047±0.020. The CeZ nanoparticles have a hydrated particle size of 412.77±2.19 nm and a polydispersity index of 0.116±0.043. The CeZ@Au nanoparticles have a hydrated particle size of 445.03±12.73 nm and a polydispersity index of 0.173±0.023.

[0009] As a further description of the above technical solution:

[0010] The transmission electron microscopy (TEM) particle size of the astragalus polysaccharide carbon quantum dots was 3.0 mm. ~The interplanar spacing of the field emission transmission electron microscope is 0.21 nm, corresponding to the (100) plane lattice of graphene.

[0011] A second objective of this invention is to provide a method for preparing a dressing that promotes the healing of diabetic foot wounds, comprising the following steps:

[0012] (I) Synthesis of core-shell surface-supported gold-cerium cascade nanozymes (CeZ@Au):

[0013] (1) Synthesis of cerium dioxide nanoparticles: 2 g of cerium nitrate hexahydrate, 800 mg of polyvinylpyrrolidone (PVP, MW = 40000, high-purity K30) and 4 mL of ultrapure water were dispersed in 60 mL of ethylene glycol and stirred at room temperature for 30 min. The mixture was then heated at 160°C for 8 h, cooled to room temperature, centrifuged, and purified with ultrapure water and anhydrous ethanol. The resulting solid was dried and further calcined in a muffle furnace at 300°C for 1 h to obtain pale yellow cerium dioxide (CeO2) nanoparticles.

[0014] (2) ZIF-8 shell coating: 50 mg of CeO2 nanoparticles obtained in step (1) were added to 10 mL of 2.44 M 2-methylimidazole methanol solution (containing 2 g 2-methylimidazole), and the mixture was ultrasonically mixed for 30 min to disperse it. Then, 10 mL of methanol solution (24 mM) containing 71.4 mg zinc nitrate hexahydrate was quickly poured into the above mixture at room temperature, and the reaction was carried out for 5 min. The solid was collected by centrifugation, purified three times with ethanol, and further dried overnight in vacuum to obtain CeO2@ZIF-8 core-shell nanoparticles (CeZ).

[0015] (3) Gold nanoparticle anchoring: 20 mg of CeO2@ZIF-8 nanoparticles obtained in step (2) were dispersed in 20 mL of methanol, 50 μL of tetrachloroauric acid trihydrate methanol solution (50 mM) was added, and another 50 μL of methanol was added. The reaction mixture was stirred at 600 rpm for 30 min. After centrifugation at 12000 rpm for 10 min, the precipitate was resuspended in 10 mL of methanol. Then 2.5 mg of sodium borohydride was added, and the reaction was continued until the solution turned wine red. The product was washed with methanol, centrifuged (12000 rpm, 10 min), and vacuum dried overnight to obtain a core-shell surface-supported gold cerium cascade nanozyme (CeZ@Au).

[0016] (II) Synthesis of Astragalus polysaccharide carbon quantum dots (CDs): CDs were synthesized using a one-step hydrothermal method. 2 g of Astragalus polysaccharide and 20 mL of water were placed in a 100 mL hydrothermal reactor. The reactor was heated at 180°C for 8 h. After the reaction solution cooled to room temperature, the clear liquid was collected by centrifugation at 10000 rpm for 10 min and then through a 0.22 μm microporous membrane. The filtered dispersion was then placed in a 500 mL container. ~ Dialysis was performed for 2 days in a 1000 Da dialysis bag to obtain Astragalus polysaccharide carbon quantum dots.

[0017] (III) Synthesis of Methacryloxycarboxymethyl Chitosan (CMCSMA): 2 g of carboxymethyl chitosan (CMCS) powder was added to 200 mL of deionized water. After the CMCS was completely dissolved, 2 mL of methacrylic anhydride was slowly added. The reaction was run at pH 8 with ice water for 8 h, and the reaction was maintained by adding 5 M NaOH. A dialysis membrane (MW=8) was used. ~ The reaction mixture (14 kDa) was dialyzed against ultrapure water at 4°C for 4 days and then lyophilized to obtain methacryloxycarboxymethyl chitosan.

[0018] (IV) Synthesis of Oxidized Dextran (ODex): 5 g of dextran was dissolved in 250 mL of deionized water, and 5 g of sodium periodate (NaIO4, 0.023 mol) was added. The mixture was stirred in the dark for 3.5 h. Then, 3 mL of ethylene glycol was added, and stirring was continued for 1 h. Dialysis (MW=8) ~ 14 kDa), freeze-dried to obtain oxidized dextran.

[0019] (V) Synthesis of dopamine-modified hyaluronic acid (HA-DA): Take 1 g of hyaluronic acid, add 90 mL of deionized water, and stir for 1 minute. ~ Dissolve in 2 h, allow to stand to defoam. Adjust pH to 5.5, add 1.16 g EDC and 0.86 g NHS, stir to dissolve, and use for HA activation. Slowly add 20 mL of dopamine (DA) aqueous solution (containing 2.86 g DA) under nitrogen atmosphere, stir at room temperature for 24 h, the color changes from powder to brown. Use 3500 ~ Dialysis was performed for 5 days using a 7000 Da dialysis bag, followed by lyophilization to obtain dopamine-modified hyaluronic acid (HA-DA).

[0020] (VI) Synthesis of (CeZ@Au / CDs)@H hydrogel: 40 mg HA-DA and 200 μg CDs were dissolved in 650 μL of deionized water, and the pH was adjusted to 8 with 1 M NaOH. The mixture was stirred for 30 min. 1250 μL of CMCSMA (40 mg / mL) was taken, 3 mg of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP) was added, and 250 μL of CeZ@Au (2 mg / mL) was added. After stirring and dissolving evenly, the mixture was mixed with the previous HA-DA solution. 375 μL of ODEX solution (40 mg / mL) was added, and the pH was adjusted to 8 with 1 M NaOH. After about 60 s, a Schiff base reaction occurred, and the solution gradually thickened. After irradiation with blue light for 90 s, the H@CeZ@Au / CDs hydrogel was obtained.

[0021] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0022] (1) This invention provides a core-shell surface-supported gold-cerium cascade nanozyme (CeZ@Au), wherein the CeO2 nanocore has dual enzyme-like activities of catalase (CAT) and peroxidase (POD) under physiological conditions, and can generate hydroxyl radicals to kill bacteria or generate O2 to improve hypoxia; the ZIF-8 shell is stable under physiological conditions, decomposes in an acidic environment and slowly releases Zn²⁺, which is beneficial to accelerate wound healing and has a certain antibacterial effect; the surface-anchored AuNPs have glucose oxidase-like (GOx) activity, which can catalyze the oxidation of glucose to produce gluconic acid and H2O2. The three functional components synergistically form a cascade nanozyme system with CAT, GOx and POD enzyme-like activities, which has not been reported before.

[0023] (2) In this invention, carbon quantum dots are prepared by hydrothermal carbonization using Astragalus polysaccharide as the carbon source, and are introduced into the composite hydrogel as a functional component to form a multifunctional composite system together with CeZ@Au.

[0024] (3) The hydrogel of the present invention is formed by a dual cross-linking network through Schiff base reaction and photocross-linking reaction, which has a stable three-dimensional network structure and good injectability (shear thinning behavior). It can be smoothly squeezed out from a 5ml fine needle syringe and can still maintain the gel structure after injection, making it suitable for filling irregularly shaped wounds.

[0025] (4) The hydrogel of the present invention has a typical honeycomb microporous structure, which is conducive to the delivery of bioactive ingredients and the provision of sufficient oxygen; it has good swelling properties and can absorb wound exudate; it has a moderate degradation rate and can be completely degraded within about 36 hours, making it suitable for use as a wound dressing.

[0026] (5) The hydrogel of the present invention can achieve self-healing without any external stimulation and has good tissue adhesion properties (adhesion strength with pig skin tissue is about 8.93 kPa), and can firmly adhere to the wound tissue. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the CeO2@ZIF-8 preparation process.

[0028] Figure 2 TEM and SEM images of CeO2NPs, CeZ, CeZ@Au, and CDs.

[0029] Figure 3 The images show the DLS, XRD, and XPS characterizations of each nanoparticle.

[0030] Figure 4 The image shows the morphology and FTIR characterization of the hydrogel.

[0031] Figure 5 The graphs show the rheological, swelling, degradation, self-healing, and tissue adhesion properties of the hydrogel. Detailed Implementation

[0032] The present invention will now be described in detail with reference to specific embodiments. These embodiments are for illustrative purposes only and should not be construed as limiting the scope of the invention. Experimental methods not specifically described in the embodiments are generally performed under conventional conditions or as recommended by the manufacturer.

[0033] The reagents used in the following examples are as follows:

[0034]

[0035] (1) Example 1: Synthesis of core-shell surface-supported gold-cerium cascade nanozyme (CeZ@Au)

[0036] 2 g of cerium nitrate hexahydrate, 800 mg of PVP and 4 mL of ultrapure water were dispersed in 60 mL of ethylene glycol, stirred at room temperature for 30 min, heated at 160°C for 8 h, cooled and centrifuged to purify, dried and calcined at 300°C for 1 h to obtain CeO2NPs.

[0037] Add 50 mg CeO2NPs to 10 mL of 2-methylimidazolium methanol solution, sonicate for 30 min, add 10 mL of zinc nitrate hexahydrate methanol solution (24 mM), react for 5 min, centrifuge, purify with ethanol, and vacuum dry to obtain CeZ.

[0038] 20 mg CeZ was dispersed in 20 mL of methanol, 50 μL of HAuCl4 methanol solution (50 mM) was added, the mixture was stirred for 30 min, centrifuged and resuspended in 10 mL of methanol, 2.5 mg of NaBH4 was added and reacted until wine red, washed with methanol, centrifuged and dried under vacuum to obtain CeZ@Au.

[0039] Morphological characterization of CeZ@Au

[0040] Monodisperse, uniformly spherical CeO2 NPs were synthesized via a solvothermal method and calcination. Figure 2 a). A liquid-phase concentration-controlled nucleation method was used to coat the CeO2NPs with a ZIF-8 shell. The shell thickness was controlled by adjusting the zinc concentration and reaction time. When the 2-methylimidazole concentration was 100 times that of zinc nitrate and the reaction time was 5 min, a clear core-shell structure CeZ was obtained, with the dark core being CeO2 and the light shell being ZIF-8. The particle size increased from 208 nm to 325 nm. Figure 2 b). The shell is not obvious at a reaction time of 1 min ( Figure 2 g), dispersed ZIF-8 particles are formed after 30 min ( Figure 2 h); when the concentrations of 2-methylimidazole and zinc nitrate were adjusted to 2.44 M and 14 mM respectively, and the reaction time was 30 min, a heterogeneous ZIF-8 shell was formed ( Figure 2 i); When the reaction time was extended to 10 min, the shell thickness did not change significantly, but the crystallization was more complete (i); Figure 2 j). AuNPs were uniformly anchored on the CeZ surface via in-situ reduction with sodium borohydride. Figure 2 c). SEM showed that CeZ@Au was spherical and uniform in size. Figure 2 d). TEM elemental surface scanning shows that Ce is located in the central region, Zn, C, and N are distributed in the shell, and Au is distributed throughout the entire particle surface. Figure 2 f). CDs exhibit good dispersibility with a particle size of 3.0 mm. ~ 5.0 nm, HRTEM interplanar spacing 0.21 nm, corresponding to the in-plane lattice of graphene (100) ( Figure 2 e). Through DLS ( Figure 3 a) The measured hydrated particle sizes of CeO2, CeZ, and CeZ@Au were 247.87±0.74 nm, 412.77±2.19 nm, and 445.03±12.73 nm, respectively, with PDI < 0.3, indicating uniform size. It is speculated that the DLS measurement of CDs was biased due to the small particle size and photoluminescent properties. Figure 3 b). XRD ( Figure 3c) Confirmed that CeO2 is a cubic fluorite phase, and ZIF-8 characteristic peaks appear after ZIF-8 coating. CeZ@Au shows Au (311) crystal plane peaks, CDs exhibit a broad graphitic carbon (002) peak at 19.5°, and the hydrogel shows polymer dispersion peaks. XPS ( Figure 3 (d, 3e) confirmed the coexistence of C, N, O, Ce, Zn, and Au elements, indicating that the ZIF-8 coating and AuNPs were successfully modified.

[0041] (2) Example 2: Synthesis of Astragalus polysaccharide carbon quantum dots (CDs)

[0042] 2 g of Astragalus polysaccharide and 20 mL of water were placed in a 100 mL hydrothermal reactor and heated at 180°C for 8 h. After cooling, the mixture was centrifuged (10000 rpm, 10 min). The supernatant was filtered through a 0.22 μm microporous membrane, and the filtrate was treated with 500 ml of water. ~ Dialysis with a 1000 Da dialysis bag for 2 days yielded CDs.

[0043] (3) Example 3: Synthesis of methacryloylcarboxymethyl chitosan (CMCSMA)

[0044] Dissolve 2 g CMCS in 200 mL of deionized water, add 2 mL MA, adjust pH to 8, and react in an ice-water bath for 8 h. ~ A 14 kDa dialysis membrane was dialyzed at 4°C for 4 days and then lyophilized to obtain CMCSMA. FTIR confirmed that CMCSMA exhibited characteristic peaks of amide I and amide II bands at 1655 cm⁻¹ and 1551 cm⁻¹, respectively. Figure 4 g).

[0045] (4) Example 4: Synthesis of oxidized dextran (ODex)

[0046] Dissolve 5 g of dextran in 250 mL of deionized water, add 5 g of NaIO4, stir in the dark for 3.5 h, add 3 mL of ethylene glycol and continue stirring for 1 h, and then... ~ Dialysis and lyophilization were performed using a 14 kDa dialysis bag to obtain 0 Dex.

[0047] (5) Example 5: Synthesis of dopamine-modified hyaluronic acid (HA-DA)

[0048] Dissolve 1 g HA in 90 mL of deionized water, adjust the pH to 5.5, add 1.16 g EDC and 0.86 g NHS for activation, and add 20 mL of DA aqueous solution (containing 2.86 g DA) dropwise under nitrogen protection. React at room temperature for 24 h, and then use 3500... ~ Dialysis was performed for 5 days using a 7000 Da dialysis bag, followed by lyophilization to obtain HA-DA.

[0049] (6) Example 6: Synthesis of (CeZ@Au / CDs)@H hydrogel

[0050] Dissolve 40 mg HA-DA and 200 μg CDs in 650 μL of deionized water, adjust the pH to 8, and stir for 30 min. Take 1250 μL of CMCSMA solution (40 mg / mL), add 3 mg LAP and 250 μL of CeZ@Au solution (2 mg / mL), mix well, and then mix with the above solution. Add 375 μL of ODEX solution (40 mg / mL), adjust the pH to 8, and after about 60 s, a Schiff base reaction occurs and the mixture thickens. Irradiate with 405 nm blue light for 90 s to obtain (CeZ@Au / CDs)@H hydrogel.

[0051] (7) Example 7: Hydrogel performance test and characterization results

[0052] The -NH in CMCSMA reacts with the -CHO in ODex via a Schiff base reaction, resulting in cross-linking and curing. Subsequent irradiation with 405 nm blue light causes further cross-linking of the CMCSMA, forming a pre-hydrogel with a stable structure. Figure 4 a). The viscosity of H@CeZ@Au / CDs hydrogel decreased significantly with increasing shear rate, exhibiting obvious shear-thinning behavior. H@CeZ@Au / CDs hydrogel could be smoothly extruded from a fine-needle syringe, indicating good injectability and the ability to maintain a solid state after injection. Figure 4 b). SEM observation showed that all hydrogels exhibited a honeycomb-like porous structure. Figure 4 c~4e), and Figure 4 Compared to the blank hydrogel, the hydrogel containing only CeZ@Au (c) Figure 4 d) and hydrogels containing CeZ@Au and CDs ( Figure 4 The pore size of (e) gradually decreases. SEM elemental surface scan analysis ( Figure 4 f) Clearly shows the distribution of elements such as Ce, Zn, and Au in the hydrogel, proving the successful loading of CeZ@Au.

[0053] Rheological tests show that at 0.1 ~ Within a frequency range of 100 rad / s, all samples have G' > G", indicating that the hydrogel has a stable and rigid structure. Figure 5 a). The hydrogel exhibits shear-thinning behavior, and the intersection of G' and G" is the gel-sol phase transition ( Figure 5 b).

[0054] Swelling tests showed that the hydrogels reached swelling equilibrium after 72 h of incubation in PBS, and all hydrogels exhibited high swelling capacity, indicating that the hydrogels have a high absorbency in absorbing tissue exudate. Figure 5 c). Degradation tests showed that the hydrogel could be completely degraded within 36 hours after reaching swelling equilibrium, and the degradation rate was moderate. Figure 5 d).

[0055] Healing tests showed that the hydrogel could heal itself upon re-contact after being cut, without any external irritation. Figure 5 e). Hydrogels can firmly adhere to various surfaces such as plastics, rubber, glass, and steel. Figure 5 f).

[0056] Tissue adhesion tests showed that ( Figure 5 (g~5h), the tissue adhesion properties of the hydrogel on pigskin were evaluated using an overlap shear test. A single-layer overlap structure was shown in... Figure 5 As shown in g, the overlap shear strength between the hydrogel and porcine skin tissue is approximately 8.93 kPa. Figure 5 h), indicating that it has good skin adhesion.

Claims

1. A multi-enzyme cascade hydrogel for repairing diabetic foot wounds, characterized in that, include: The core-shell surface-supported gold-cerium cascade nanozyme comprises astragalus polysaccharide carbon quantum dots, methacryloxycarboxymethyl chitosan, dopamine-modified hyaluronic acid, oxidized dextran, and a photoinitiator. The core-shell surface-supported gold-cerium cascade nanozyme has a cerium dioxide nanocore, a ZIF-8 shell coating the surface of the cerium dioxide nanocore, and gold nanoparticles anchored to the surface of the ZIF-8 shell. The hydrogel is formed by Schiff base reaction and photocrosslinking reaction.

2. The multi-enzyme cascade hydrogel according to claim 1, characterized in that: The preparation method of the core-shell surface-supported gold-cerium cascade nanozyme includes the following steps: (1) 2 g of cerium nitrate hexahydrate, 800 mg of polyvinylpyrrolidone and 4 mL of ultrapure water were dispersed in 60 mL of ethylene glycol, stirred at room temperature for 30 min, heated at 160°C for 8 h, cooled and centrifuged, purified with ultrapure water and anhydrous ethanol, dried and calcined in a muffle furnace at 300°C for 1 h to obtain cerium dioxide nanoparticles. (2) Add 50 mg of cerium dioxide nanoparticles obtained in step (1) to 10 mL of 2-methylimidazolium methanol solution with a concentration of 2.44 M, disperse by ultrasonication for 30 min, then add 10 mL of methanol solution (24 mM) containing 71.4 mg zinc nitrate hexahydrate, react for 5 min, collect the solid by centrifugation, purify with ethanol 3 times, and vacuum dry overnight to obtain CeZ nanoparticles; (3) Disperse 20 mg of CeZ nanoparticles obtained in step (2) in 20 mL of methanol, add 50 μL of 50 mM tetrachloroauric acid methanol solution, stir for 30 min, add 2.5 mg of sodium borohydride, react until the solution turns wine red, wash with methanol, centrifuge (12000 rpm, 10 min), and vacuum dry overnight to obtain core-shell surface-supported gold-cerium cascade nanozyme.

3. The multi-enzyme cascade hydrogel according to claim 2, characterized in that: In step (2), the molar ratio of 2-methylimidazole to zinc nitrate is 100:1, and the reaction time is 5 min.

4. The multi-enzyme cascade hydrogel according to claim 2, characterized in that: In step (3), sodium borohydride is added and the reaction continues until the solution turns wine red, which is the endpoint of the reaction.

5. The multi-enzyme cascade hydrogel according to claim 1, characterized in that: The preparation method of the carbon quantum dots of Astragalus polysaccharide is as follows: 2 g of Astragalus polysaccharide and 20 mL of water are placed in a hydrothermal reactor and heated at 180°C for 8 h. After cooling, the mixture is centrifuged (10000 rpm, 10 min). The supernatant is filtered through a 0.22 μm microporous membrane, and the filtrate is placed in a 500 mL container. ~ Dialysis in a 1000 Da dialysis bag for 2 days yielded Astragalus polysaccharide carbon quantum dots.

6. The multi-enzyme cascade hydrogel according to claim 1, characterized in that: The preparation method of the methacryloylcarboxymethyl chitosan is as follows: 2 g of carboxymethyl chitosan is dissolved in 200 mL of deionized water, 2 mL of methacrylic anhydride is added, and the mixture is reacted at pH=8 under ice-water bath conditions for 8 h. ~ A 14 kDa dialysis bag was dialyzed against ultrapure water at 4°C for 4 days, followed by lyophilization to obtain methacryloylcarboxymethyl chitosan.

7. The multi-enzyme cascade hydrogel according to claim 1, characterized in that: The preparation method of the oxidized dextran is as follows: 5 g of dextran (molecular weight 70,000) is dissolved in 250 mL of deionized water, 5 g of sodium periodate is added, and the mixture is stirred in the dark for 3.5 h. Then, 3 mL of ethylene glycol is added and stirring is continued for 1 h. ~ Dialysis was performed using a 14 kDa dialysis bag, followed by freeze-drying to obtain oxidized dextran.

8. The multi-enzyme cascade hydrogel according to claim 7, characterized in that: The molar ratio of sodium periodate to glucose units in dextran is 0.77:1, the reaction time is 3.5 hours, and the entire process is conducted in the dark.

9. The multi-enzyme cascade hydrogel according to claim 1, characterized in that: The preparation method of the dopamine-modified hyaluronic acid is as follows: 1 g of hyaluronic acid (molecular weight 20) is added to the hyaluronic acid solution. ~ Dissolve 400,000 units of dopamine in 90 mL of deionized water, adjust the pH to 5.5, add 1.16 g of EDC and 0.86 g of NHS for activation, and slowly add 20 mL of an aqueous solution containing 2.86 g of dopamine under nitrogen protection. Stir the reaction at room temperature for 24 h, and then use 3500... ~ Dialysis was performed for 5 days using a 7000 Da dialysis bag, followed by lyophilization to obtain dopamine-modified hyaluronic acid.

10. The method for preparing the multi-enzyme cascade hydrogel according to claim 1, characterized in that, Includes the following steps: 40 mg of dopamine-modified hyaluronic acid and 200 μg of Astragalus polysaccharide carbon quantum dots were dissolved in 650 μL of deionized water, and the pH was adjusted to 8 with 1 M NaOH and stirred for 30 min. Take 1250 μL of methacryloylcarboxymethyl chitosan with a concentration of 40 mg / mL, add 3 mg of photoinitiator lithium phenyl (2,4,6-trimethylbenzoyl) phosphate, add 250 μL of core-shell surface-supported gold-cerium cascade nanozyme with a concentration of 2 mg / mL, stir to dissolve, and mix with the above dopamine-modified hyaluronic acid solution. Add 375 μL of oxidized dextran solution with a concentration of 40 mg / mL, adjust the pH to 8 with 1 M NaOH, and allow the mixture to thicken after about 60 s of Schiff base reaction. Irradiate with 405 nm blue light for 90 s to obtain the multi-enzyme cascade hydrogel.

11. The method for preparing the multi-enzyme cascade hydrogel according to claim 10, characterized in that: The Schiff base reaction thickened approximately 60 seconds after the pH was adjusted to 8, and the blue light irradiation time was 90 seconds.

12. The use of the multi-enzyme cascade hydrogel according to any one of claims 1 to 11 in the preparation of a drug or medical dressing for repairing diabetic foot wounds.